2019
DOI: 10.1016/j.inffus.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive overview of biometric fusion

Abstract: The performance of a biometric system that relies on a single biometric modality (e.g., fingerprints only) is often stymied by various factors such as poor data quality or limited scalability. Multibiometric systems utilize the principle of fusion to combine information from multiple sources in order to improve recognition accuracy whilst addressing some of the limitations of singlebiometric systems. The past two decades have witnessed the development of a large number of biometric fusion schemes. This paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(79 citation statements)
references
References 197 publications
(269 reference statements)
0
78
0
1
Order By: Relevance
“…Hot topics integrating data quality, soft biometrics, approaches to enhance the accuracy of biometric recognition to prevent security attacks using cryptosystems were also discussed. Authors concluded their review while addressing the research challenges concerning biometric based fusion systems [18]. Gunasekaran et al (2019) proposed a biometric recognition system that used Contour let Transform Model for pre-processing followed by Local Derivative Ternary Pattern model to improve recognition based on pre-processed features.…”
Section: Singh Et Al (2019)mentioning
confidence: 99%
“…Hot topics integrating data quality, soft biometrics, approaches to enhance the accuracy of biometric recognition to prevent security attacks using cryptosystems were also discussed. Authors concluded their review while addressing the research challenges concerning biometric based fusion systems [18]. Gunasekaran et al (2019) proposed a biometric recognition system that used Contour let Transform Model for pre-processing followed by Local Derivative Ternary Pattern model to improve recognition based on pre-processed features.…”
Section: Singh Et Al (2019)mentioning
confidence: 99%
“…AlexNet is considered as the first state-of-the-art deep learning approach after it outperformed traditional computer vision methods in terms of accuracy and recognition rates [41]. It is the most well-studied CNN architecture due to its impact in most image classification tasks [42]. The architecture and network design of AlexNet is composed of 8 sequential layers with ~60 million parameters for a total of 25 layers.…”
Section: ) Alexnetmentioning
confidence: 99%
“…The previous two decades have seen the improvement of an extensive number of biometric and multi biometric cryptosystems which was talked about for the acknowledgment of a person for security reason. Maneet Singh et al [13] have exhibited an outline of biometric combination with explicit spotlight on three inquiries: what to fusion, when to wire, and how to interlink. A complete survey of methods fusing auxiliary data in the biometric acknowledgment pipeline was additionally introduced.…”
Section: A Submission Of the Papermentioning
confidence: 99%